Msti za gore naroda! - Ivanov, Viktor Semonovich (Изобразительное искусство, 1943)
Elderly peasant woman with closed fist and destroyed village behind Original title: Мсти за горе народа! Suggested translation: Revenge for the grief of the people! PO-0060